The relationship between attachment style, personality traits and career decision self-efficacy among students - Mohamad Yusop, Yusni; Ting, Tan Yan; Zainudin, Zaida Nor; Wan Othman, Wan Norhayati; Puad Mohd Kari, Dharatun Nissa; Surat, Shahlan; Abdul Ghafar, Nurul Nadia (Human Resource Management Academic Research Society, 2022)
The objective of the study is to examine the relationship between attachment style, personality traits, and career decision self-efficacy. T-test is used to compare the gender differences, while Pearson’s Correlation is used to identify the relationship between the variables. A sample of 92 postgraduate students in the faculty of education at Universiti Putra Malaysia is involved in the study. three instruments were used: Career Decision Self-Efficacy Short Form (CDSE-SF), Relationship Scale Questionnaire (RSQ), and Big Five Inventory (BFI44). The finding reported that there are no significant differences between males and females towards career decision self-efficacy, it refers to gender does not affect the level of CDSE. Furthermore. The results showed there was a significant relationship between secure attachment and career decision self-efficacy (r=.335, p=.000). A significant relationship is identified between the personality traits of Openness (r=.413, p=.000), Conscientiousness (r=.408, p=.000), and Neuroticism (r=-.311, p<.05). In conclusion, there is a significant relationship between some of the sub-scales from each variable in the present study.